Morphological characteristics and biological maturation of Brazilian and Portuguese gymnasts - Batista, A.; Garganta, R.; Avila-Carvalho, L. (International Journal of Morphology, 2019)
The morphological characteristics and biological maturation are among the more important factors in the performance in the Rhythmic Gymnastics. Thus, the aims of the present study were: (1) identify the training, morphological and biological maturation characteristics in elite Brazilian and Portuguese gymnasts; (2) compare these characteristics across groups. The Brazilian Portuguese National Team (13 gymnasts) were studied. Anthropometric and body composition measurements were performed. For analysis of biological maturation, the sexual (pubertal stages and age at menarche) and somatic (offset maturational) maturation were evaluated. The training data were collected by interviewing. For the statistical analysis, Mann-Whitney test was applied. The somatotype and calculation of its components were performed according to the Health-Carter method thought of the MER Goulding Software Development. Brazil and Portugal National Teams presented similar training volume and training onset, however Brazilian gymnasts had higher age and years of practice in Rhythmic Gymnastics than Portuguese gymnasts. Brazilian had higher body mass; height; lower limb length; triceps, subscapular and abdominal skinfolds; relaxed arm and thigh girths; and endomorphy somatotype component than Portuguese. The groups showed different somatotypes: Brazilian (endomorphic ectomorph) and Portuguese (balanced ectomorph), although without statistical significance. The groups demonstrated a delay in maturational development. Similar breast (stages 3 and 4) and pubic hair (stages 2 and 3) development were verified. In total, 84.6 % of gymnasts had reached menarche (15.9±2.6 years) and all gymnasts had reached the age at peak height velocity (14.9±1.2 years). The distance and age at peak height velocity were higher in Brazilian than in Portuguese.